Juan Luis Vives sobre la elocución retórica: conceptos y composición del párrafo - Sánchez Manzano, María Asunción (eHumanista: Journal of Iberian Studies, 2014)
This article analyzes Vives's impressive background in his knowledge of classical rhetoric. We explore his efforts to reproduce, interpret, and criticize the tradition in his written compositions. As a consequence, he shows a perfect comprehension of the value of classical rhetoric. The connection of thought and expression is designed to produce models of vivid and complete elocutio.